Currency Crises and Commodity Markets: Dynamic Relationships and Implications for Sustainable Investing and International Trade - Mohd. Khan, Caroline (European Journal of Sustainable Development, 2025)
This study examines the inter-relation between WTI crude oil futures prices and two energy-related exchange-traded funds (ETFs): the ETF of iShares Global Clean Energy (Clean Energy) and the ETF of Energy Sector SPDR Fund (Traditional Energy). Using Granger causality tests and the Dynamic Conditional Correlation Generalized Autoregressive Conditional Heteroskedasticity (DCC-GARCH) model, we analyze causal relationships and volatility transmission between these assets. The Granger causality results show that traditional energy markets dominate, while clean energy markets are becoming more influential on crude oil futures prices. Clean energy markets Granger-causes crude oil futures prices while traditional energy markets strongly Granger-causes crude oil futures. Clean energy ETFs have lower volatility persistence than conventional energy ETFs, according to the DCC-GARCH data, which also demonstrate time-varying correlations. Important insights for sustainable investment, energy policy, and risk management in the context of the world’s energy transition are provided by these results, which emphasize the monetary interdependencies between energy ETFs and crude oil futures prices. Keywords: Crude oil futures prices, Clean energy ETFs, Traditional energy ETFs, Granger causality, DCC-GARCH, Sustainable Investing